2006
DOI: 10.1245/s10434-006-9120-y
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Effect of Micrometastases in Previously Staged Lymph Node Negative (N0) Colorectal Carcinoma: A Meta-analysis

Abstract: The prognostic value of micrometastases detected retrospectively by RT-PCR is significant in AJCC stage II colorectal patients. Studies utilizing RT-PCR performed a more complete nodal analysis when compared to studies using IHC techniques. RT-PCR may also be more specific for the detection of clinically relevant micrometastases compared to IHC detected cytokeratins. Prospective studies are needed to evaluate the potential benefit of systemic chemotherapy in patients with molecular metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
141
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(145 citation statements)
references
References 39 publications
0
141
0
4
Order By: Relevance
“…In spite of the potentially curative resection, about 15-30% of patients with stage II disease will eventually develop recurrent locoregional disease or distant metastases within 5 years (Koebrugge et al 2011). Possibly, other high-risk factors can influence or predict the outcome in patients with stage II colon cancer, and further research seems warranted (Iddings et al 2006, van Schaik et al 2009, Bilchik et al 2010. The elucidation of the molecular biology of cancer cells is currently being exploited to develop potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the potentially curative resection, about 15-30% of patients with stage II disease will eventually develop recurrent locoregional disease or distant metastases within 5 years (Koebrugge et al 2011). Possibly, other high-risk factors can influence or predict the outcome in patients with stage II colon cancer, and further research seems warranted (Iddings et al 2006, van Schaik et al 2009, Bilchik et al 2010. The elucidation of the molecular biology of cancer cells is currently being exploited to develop potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…A média de idade encontrada nesse estudo foi de 61 anos, próxima à média de idade encontrada em outras séries 1,5,6,8,9,24,27,28 , sendo o risco desse câncer tanto maior quanto maior a faixa etária, uma vez que mais de 50% dos casos ocorrem em indivíduos com mais de 50 anos 29 .…”
Section: Discussionunclassified
“…Metástases linfonodais são o fator prognóstico mais importante no CCR, de forma que a investigação patológica, além da avaliação histológica de rotina de linfonodos, pode identificar maior número de pacientes com alto risco de recorrência 28 .…”
Section: Média De Gânglios Dissecados Média De Gânglios Positivosunclassified
“…Both are circumstances that limit their widespread use. Another advanced technique, the application of immunohistochemical staining methods for the detection of micrometastes is expensive and failed to prove a significant difference concerning 3-year disease-free survival in a meta-analysis performed by Iddings et al 18 In contrast confirmation of micrometastes using RT-PCR showed a significant smaller 3-year disease-free survival and reduced overall survival in positive cases.…”
Section: Discussionmentioning
confidence: 99%